Invasive Candida Infection after Upper Gastrointestinal Tract Surgery for Gastric Cancer. (6th November 2017) - Brotfain, Evgeni; Sebbag, Gilbert; Friger, Michael; Kirshtein, Boris; Borer, Abraham; Koyfman, Leonid; Frank, Dmitry; Bichovsky, Yoav; Peiser, Jochanan G.; Klein, Moti
Abstract : Upper gastrointestinal tract (GIT) surgical procedures are more likely to cause nosocomial Candida peritonitis than lower GIT procedures and they thus constitute an independent risk factor for mortality. Because of the severity of postsurgical fungal infections complications, intensivists and surgeons need to be extremely aware of their clinical importance in critically ill postsurgical intensive care unit (ICU) patients. We analyzed the clinical and microbiological data of 149 oncologic patients who were hospitalized in the ICU at Soroka Medical Center between January 2010 and January 2015 after undergoing upper GIT surgery for gastric cancer. Invasive fungal infections related to secondary peritonitis following oncologic upper GIT surgery had a higher mortality rate than patients with nonfungal postoperative infectious complications. The presence of gastroesophageal junction leakage and advanced age were found to be independent risk factors for invasive fungal infection after oncologic upper GIT surgery.